Comprehensive Strategies for Overcoming Barriers in Ocular Drug Delivery: Current Trends and Future Directions - N, Elavarasan; Revathi, S.; Venkateshwaran, K. (Biomedical Sciences and Clinical Medicine, 2025)
The human eye is a complex and sensitive organ, making effective drug delivery a major challenge. Its anatomical barriers, such as the precorneal, corneal, and blood-ocular barriers, significantly limit drug penetration and retention. Researchers have long focused on improving topical delivery methods to enhance drug absorption and prolong therapeutic action. Various ocular drug delivery routes have been explored, including subconjunctival, intracameral, intraocular, juxta-scleral, intravitreal, and retrobulbar. Despite these efforts, about 95.0% of available ophthalmic formulations are only available in liquid form. Other dosage forms include solids (powders, inserts, lenses), semi-solids (ointments, gels), and hybrids like in-situ gels. Nanotechnology-based carriers have recently emerged as promising tools in ocular drug delivery. These systems improve drug stability, enhance bioavailability, increase ocular permeability, and extend residence time. Additionally, they are capable of encapsulating both hydrophilic and lipophilic drugs, making them highly versatile. Various characterization methods such as in vitro, ex vivo, and in vivo studies are being used to assess the performance of these nanocarriers. This review aims to highlight the anatomical complexities of the eye, current challenges in ocular drug delivery, and the advantages and limitations of various dosage forms and routes. It also discusses recent advancements in nanotechnology-based drug delivery systems.